Towards materials discovery: assays for screening and study of chemical interactions of novel corrosion inhibitors in solution and coatings. (24th April 2020) - White, Paul A.; Collis, Gavin E.; Skidmore, Melissa; Breedon, Michael; Ganther, Wayne D.; Venkatesan, Kishore
Abstract : Using chemical design, computational modelling, structure–activity and structure–property relationships, with high-throughput solution and coating assays we can rapidly identify prime corrosion inhibitor candidates for further detailed evaluation. Abstract : The discovery of novel corrosion inhibitors for solution and coating applications is still an empirical process because of the large number of parameters that impact efficacy and the varied environmental conditions in which inhibitors are deployed. Moreover, conventional methods such as electrochemical and analytical techniques, and coating standard specifications can be extremely end-use focused, time and material intensive, and costly, making it prohibitive to screen new materials quickly at early stages of the discovery process. In an effort to address these challenges, we have continued to develop and deploy models and assays that can assist in accelerating the materials discovery process around novel corrosion inhibitors for different metals. In this paper we present how computational modelling, coupled with high-throughput optical and high-throughput electrochemical solution and coating assays, can be powerful tools that allow the rapid identification of prime candidates for further study. These experimental techniques are consistent with conventional % inhibition efficiency and neutral salt spray measurements, and provide additional and insightful information that cannot be easily or quickly obtained by traditional methods. Information extracted from the study of these chromium-based and small organic heterocyclic compounds reveals interesting structure–activity and structure–property relationships that will be applied in the design and discovery of new corrosion inhibitors.